Futurist Art: Motion and Aesthetics As a Function of Title - Mastandrea, Stefano; Umiltà, Maria A. (Frontiers in Human Neuroscience, 2016)
Very often the titles of Futurist paintings contain words denoting movement in order to satisfy their artistic poetic focused on motion and velocity. The aim of the present study is to investigate the reported dynamism and aesthetic quality of several Futurist artworks as a function of their title. Ten Futurist artworks with a movement-related word in the title were selected for this study. The titles were manipulated, resulting in four conditions for each painting: the “original title” with the movement word; an “increased” title in which an adjective was added in order to intensify the sense of dynamism; a “decreased” title, in which the movement word was eliminated; no title. Participants evaluated the movement suggested by each painting in the four different title conditions, rated their beauty and reported how much they liked the work. Results showed that the manipulation of the title had an effect on the reported movement: compared to the others, paintings presented with the “original” and with the “increased” title received significant higher movement scores. Of interest, beauty did not differ across conditions, but liking was higher for the conditions with more movement. Lastly, positive correlations between the quantity of perceived movement and aesthetic evaluation were found. From the present results it can be concluded that Futurists attributed much relevance to the titles of their artworks in order to effectively increase the expression of the movement represented.